KAJIAN TENTANG PEMBENTUKAN HUKUM SINERGI DENGAN DINAMIKA MASYARAKAT DAN KEBUDAYAAN - Astuti, Dwi (Wacana Hukum, 2010)
Abstract The law is always related to society and behavior-behavior in the context of social interaction. The law is also closely related to social values and cultural values of society. Because no other good law is the law that reflects the values of living in society. Key words : Establishment of law, society and cultural dynamics